2020
DOI: 10.1111/cge.13846
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the nosology of osteogenesis imperfecta

Abstract: Osteogenesis imperfecta (OI) is a relatively common genetic skeletal disorder with an estimated frequency of 1 in 20 000 worldwide. The manifestations are diverse and although individually rare, the several different forms contribute to the production of a significant number of affected individuals with considerable morbidity and mortality. During the last decade, there have been extensive molecular investigations into the etiology of OI and these advances have direct relevance to the medical management of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
0
29
0
2
Order By: Relevance
“…Many authors [ 26 ], even today, in an attempt to understand what are the characteristic malformations of the pathology and in an attempt to find solutions, have dwelt on the malocclusion pictures [ 27 , 28 , 29 ], but have not deepened the morphological variation related to the mandible and the chin region. Instead, our study has, as a primary objective, searched for new correlation indices between anatomical variations of the chin and alveolar bone symphysis and the severity of the disease in order to find more defined anatomical details.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors [ 26 ], even today, in an attempt to understand what are the characteristic malformations of the pathology and in an attempt to find solutions, have dwelt on the malocclusion pictures [ 27 , 28 , 29 ], but have not deepened the morphological variation related to the mandible and the chin region. Instead, our study has, as a primary objective, searched for new correlation indices between anatomical variations of the chin and alveolar bone symphysis and the severity of the disease in order to find more defined anatomical details.…”
Section: Discussionmentioning
confidence: 99%
“…They have in common that they all, via different mechanisms, affect the quality or quantity of type I collagen, the main protein component of the skeleton. However, the spectrum of mechanisms ultimately leading to defective collagen assembly in the extracellular matrix has expanded considerably recently, necessitating several revisions in classifications (13,14). In most cases, studies on disease mechanisms in vitro and in animal models have indicated defects in collagen secretion and structure, procollagen transport, folding, post-translational modification, processing and crosslinking.…”
Section: Monogenic Low Bone Mass Disordersmentioning
confidence: 99%
“…With the advance of molecular biology, the categories of OI were expanded according to comprehensive radiographic, bone morphologic features, and molecular etiology, which has expanded to type XX. 5) These classification systems have limitations related to variable extraskeletal features, such as hearing impairment, blue sclera, DI, and wormian bones. 4,6,7) In order to assess clinical severity in different types of OI, the clinical scoring system has been proposed.…”
Section: Introductionmentioning
confidence: 99%